Readability assessment of online thyroid surgery patient education materials. Issue 10 (13th September 2012) - Patel, Chirag R.; Cherla, Deepa V.; Sanghvi, Saurin; Baredes, Soly; Eloy, Jean Anderson
<x xml:space="preserve">Abstract</x> Background Published guidelines recommend written health information be written at or below the sixth‐grade level. We evaluate the readability of online materials related to thyroid surgery. Methods Thyroid surgery materials were evaluated using Flesch Reading Ease Score (FRES), Flesch Kincaid Grade Level (FKGL), Gunning Frequency of Gobbledygook (GFOG), and Simple Measure of Gobbledygook (SMOG). Results Thirty‐one documents were evaluated. FRES scores ranged from 29.3 to 67.8 (possible range = 0 to 100), and averaged 50.5. FKGL ranged from 6.9 to 14.9 (possible range = 3 to 12), and averaged 10.4. SMOG scores ranged from 11.8 to 14.5 (possible range = 3 to 19), and averaged 13.0. GFOG scores ranged from 10.6 to 18.0 (possible range = 3 to 19), and averaged 13.5. Conclusions Readability scores for online thyroid surgery materials are higher (i.e., more difficult) than the recommended levels. However, readability is only one aspect of comprehension. Written information should be designed with that fact in mind. © 2012 Wiley Periodicals, Inc. Head Neck 35: 1421–1425, 2013